2012
DOI: 10.5539/ijef.v4n6p198
|View full text |Cite
|
Sign up to set email alerts
|

Oil Prices and the Real Exchange Rate in Nigeria

Abstract: This paper has investigated the relationship between the real oil prices and the Real Exchange Rate. Using time series data covering the period between 1980 and 2010, the result of the Johansen cointegration test suggests a long run equilibrium relationship between the real oil prices and the Real Exchange Rate. This relationship was supported by the Granger Causality test which validated the causal relationship from the real oil prices to the Real Exchange Rate. The result from the Generalized Autoregressive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 12 publications
0
13
1
Order By: Relevance
“…Moreover, analysis of generalized impulse response function reveals that impact of oil price on exchange rate is significant after 2008 financial crisis. Adeniyi et al [58] analyzed the relationship between oil prices and exchange rate using GARCH and exponential GARCH (EGARCH) in case of Nigeria. They found that oil price rise appreciates Nigerian currency against US dollar and same inference was drawn by Olomola and Adejumo, [10] and latter on by Oriavwote and Eriemo, [59] 12 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, analysis of generalized impulse response function reveals that impact of oil price on exchange rate is significant after 2008 financial crisis. Adeniyi et al [58] analyzed the relationship between oil prices and exchange rate using GARCH and exponential GARCH (EGARCH) in case of Nigeria. They found that oil price rise appreciates Nigerian currency against US dollar and same inference was drawn by Olomola and Adejumo, [10] and latter on by Oriavwote and Eriemo, [59] 12 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, the consequence of oil prices on exchange rate movements has been emphasized by Amano and Van Norden (1998) and recently has been renewed by several authors, as Kin and Courage (2014), Oriavwote and Eriemo (2012), Basher et al (2011), Aziz (2009). Such studies argue that increases in the oil price of the oil-exporter (oil importer) lead to an increase (decrease) in the relative price of commodities.…”
Section: Introductionmentioning
confidence: 99%
“…This oil price volatility is so severe that the Nigerian budget is even at some point in time tied up to a particular benchmark price of crude oil. The budget has been adjusted in so many occasions when there is a sudden change in crude oil prices such as the reduction of budget due to a fall in oil prices during the global financial crisis (Oriavwote and Eriemo, 2012).…”
mentioning
confidence: 99%